2010
DOI: 10.1017/s1368980010002521
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional adequacy of three dietary patterns defined by cluster analysis in 997 pregnant Japanese women: the Osaka Maternal and Child Health Study

Abstract: Objective: To examine the adequacy and inadequacy of dietary patterns in pregnant women for which information is absolutely lacking. Design: Diet was assessed by a validated, self-administered diet history questionnaire (DHQ). Dietary patterns were extracted from the intake of thirty-three food groups (g/4184 kJ (1000 kcal)), which were summarized from 147 foods assessed with the DHQ, by cluster analysis. Nutritional inadequacy for selected twenty nutrients in each dietary pattern was examined using the refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
90
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 32 publications
7
90
2
2
Order By: Relevance
“…Moreover, to the best of our knowledge, no research has yet been conducted on the relationship between dietary intake and gut microbiota in young Japanese women. These women have low protein and dietary fi ber intake and show diversity in their dietary intake with four main patterns previously identifi ed (21). Recent reports have shown a correlation between dietary patterns and constipation (22), so the gut microbiota of young Japanese women could be associated with dietary intake.…”
mentioning
confidence: 95%
“…Moreover, to the best of our knowledge, no research has yet been conducted on the relationship between dietary intake and gut microbiota in young Japanese women. These women have low protein and dietary fi ber intake and show diversity in their dietary intake with four main patterns previously identifi ed (21). Recent reports have shown a correlation between dietary patterns and constipation (22), so the gut microbiota of young Japanese women could be associated with dietary intake.…”
mentioning
confidence: 95%
“…Dietary habits during the preceding month were assessed using a previously validated DHQ (2,3,(11)(12)(13).…”
Section: Methodsmentioning
confidence: 99%
“…The estimated average requirement (EAR) of folate has been set as 400 mg/d (1). However, the EAR of folate for pregnant Japanese women is likely to be higher than the real requirement because nutrient intake surveys (2,3) have reported that the intake of folate of pregnant women was approximately 250 mg/d, which is considerably less than the EAR of 400 mg/d. However, there are no reports on deficiency of folate in Japan.…”
mentioning
confidence: 94%
“…[37][38][39] Cluster analyses have been used by public health researchers and practitioners to inform interventions related to behaviors such as exercise, diet, and social involvement. [40][41][42] However, to our knowledge, these techniques have not been recently used to segment college populations according to current risk behaviors related to substance use.…”
Section: Introductionmentioning
confidence: 99%